Host preference fruit flies Bactrocera carambolae (Drew & Hancock) and Bactrocera dorsalis (Drew and Hancock) (Diptera: Tephritidae) - Dodin Koswanudin; Adi Basukriadi; I Made Samudra; Rosichon Ubaidillah (Perhimpunan Entomologi Indonesia, 2018)
Host plant preference amongst several fruit species was studied for two fruit fly species i.e. Bactrocera carambolae (Drew & Hancock) and Bactrocera dorsalis (Drew & Hancock), which both belong to B. dorsalis species complex. Both fruit fly species are known to be polyphagous and cause significant economic losses as pests of fruit crops. The aim of this research was to assess the host range of these major pests in Indonesia. The research was conducted at the Entomology Laboratory and Insect Specimen Collection Laboratory, Indonesian Center for Agriculture Biotechnology and Genetic Resource Research and Development, Bogor, West Java, Indonesia from June 2011 to March 2012. Comparative host preference for both species was studied with regard to malaya varieties of star fruit (Averrhoa carambolae), manalagi varieties of mango (Mangifera indica), guava aka water apple (Psidium guajava), citra water guava (Eugenia aquae), jamaica bol guava (Eugenia malaccenensis), and california papaya (Carica papaya). Our results suggest the strongest preference for malaya star fruit by B. carambolae followed by manalagi mango; and for california papaya followed by manalagi mango by B. dorsalis. The study also found that welahan variety star fruit is least preferred by both species of fruit fly.